Survey upon satisfaction of customers using services of travel agencies from Lublin province as a key element of contemporary marketing - Julia Wojciechowska-Solis (Polityki Europejskie, Finanse i Marketing)
Article addresses an issue of the relationship between the level of service quality and the customer satisfaction who decided to purchase it. The paper presents results of survey carried out by means of Servqual method in 2012 among 200 customers of travel agencies from Lublin region. The aim of the study was to determine the level of customer’s satisfaction with the services provided by travel agencies (determination of the difference between the quality of service provided by travel agencies and the quality expected by customers). Based on the study, it is concluded that the level of satisfaction with the services is satisfactory to customers, although the difference between provided and expected quality of services forces the travel agency owners to take into considerations that there are critical points that require their immediate intervention to maintain the current level of customer’s interest in their services. Significant impact on the level of customer satisfaction has the financial dimension of the service package as well as trust and professionalism of the staff.